Exploring teachers’ attitudes and self-efficacy beliefs for implementing student self-assessment of English as a foreign language writing - Zhang, Xiaoyu Sophia; Zhang, Lawrence Jun; Parr, Judy M.; Biebricher, Christine (Frontiers in Psychology, 2022)
With the growing need to nurture students’ independent learning, English language teaching (ELT) practices should reflect student-centred assessment approaches, such as self-assessment, an ultimate goal of higher education. It has been pointed out that to conduct effective self-assessment, students need to be taught systematically, and that is where teachers are expected to step in. Prior to implementing such a change in ELT, it is important to conduct research on EFL teachers’ attitudes toward, and self-efficacy beliefs about, implementing self-assessment to cultivate capable student self-assessors. Although the strong global endorsement of self-assessment over the past two decades has witnessed its classroom implementation in different disciplines, such studies are scant in relation to EFL writing classrooms. To address this gap, the present qualitative research examined five Chinese tertiary EFL writing teachers’ attitudes toward and self-efficacy beliefs about student self-assessment of writing, as well as possible reasons that discourage them from engaging students in self-assessment practices. Data collected from in-depth, semi-structured interviews indicated that self-assessment, a critical element of self-regulated learning, is surprisingly missing from the teachers’ knowledge base and previous practices. Additionally, the findings offer insights into the striking differences in teachers’ understanding of, attitudes toward, and low self-efficacy beliefs about self-assessment of writing. Reasons why teachers choose not to implement self-assessment of writing are also discussed. Findings from this study contribute to a deeper understanding of how EFL teachers’ attitudes and self-efficacy beliefs are enacted in relation to their classroom assessment practices in order to move forward discussions on the feasibility of implementing self-assessment of writing in tertiary EFL classrooms.